Exploring climate change adaptation and mitigation priorities in the South-eastern Asia’s rice market segments using GloMIP - Bayot, R.; Connor, M. (2024)
Rice production is vital for food security in South-eastern Asia (SEA), which faces significant climate crises, including drought, flood, rising temperature and rainfall variability. There is a need to review and explore the current seed product market segmentation and the corresponding target product profiles to identify future requirements that could enhance climate mitigation and adaptation efforts. The Global Market Intelligence Platform (GloMIP) was used to review the current rice market segments in South-eastern Asia and future requirements to enhance climate resilience and adaptation. Furthermore, a literature review was conducted to gather insights on recent research on farmers’ needs and climate scenarios. Currently, there are 50 rice market segments in SEA. Four have an active breeding pipeline, covering a combined total area of 16.7 million ha. The analysis highlights the importance of early maturing and direct seeded rice (DSR) in climate change adaptation and mitigation. About 11 million ha rice in Vietnam and Myanmar could shift from transplanting to DSR due to its potential to address climate-related risks. Moreover, agronomic traits, such as nutrient-use efficiency, water-use efficiency, weed-suppressing ability, and germination under moisture stress are important for DSR and recommended to be reflected in the Target Product Profiles. This review process of the current market segments is important to identify priorities within and across impact areas, and recommend necessary adjustments for the future market segments.